After a major dive, geothermal power is growing rapidly. Issue 5 (December 2015) - Janczik, Sebastian; Kaltschmitt, Martin
Abstract : The World-Market Status special report – Although still relatively small, the geothermal market has shown strong growth in 2015, and some favorable condition may soon give it a boost. The pacific "ring of fire" countries are the sole manufacturers of geothermal power, with the US leading as the biggest single producer of electricity from geothermal energy.